PHYSICAL ACTIVITY AND EXERCISE AS A KEY FACTOR IN SUCCESSFUL AGING - Angelina Passaro; Eleonora Capatti; Edoardo Dalla Nora (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2018)
Aging is associated with several changes in body composition and metabolism, including sarcopenia, sarcopenic obesity and decrease in bone mass; aerobic capacity, muscle mass and strength tend to decline progressively. These changes have considerable impact on the ability to perform daily activities, especially when associated with chronic diseases, such as type 2 diabetes, cardio-vascular disease and dyslipidemia, as well as geriatric syndromes, like mobility impairment, falls and frailty. Scientific research has shown that physical activity and exercise can slow the physiological aging clock. Particularly, active elderly people seem to age "successfully" compared to sedentary ones. The aim of our work is to review evidence-based recommendations for physical activity, exercise and diet that would help to preserve muscle mass and strength, and to reduce the gain of fat mass in older adults. Increasing levels of physical activity, in particular resistance training mixed with aerobic exercise, and adequate protein nutrition intake should be an integral component in the prevention and treatment of sarcopenia, sarcopenic obesity and metabolic syndrome in elderly subjects.